Food safety management : a practical guide for the food industry. - Andersen, Veslemøy; Lelieveld, H. L. M.; Motarjemi, Yasmine (Academic Press, 2022)
Food Safety Management: A Practical Guide for the Food Industry, Second Edition continues to present a comprehensive, integrated and practical approach to the management of food safety throughout the production chain. While many books address specific aspects of food safety, no other book guides you through the various risks associated with each sector of the production process or alerts you to the measures needed to mitigate those risks. This new edition provides practical examples of incidents and their root causes, highlighting pitfalls in food safety management and providing key insights into different means for avoiding them. Each section addresses its subject in terms of relevance and application to food safety and, where applicable, spoilage. The book covers all types of risks (e.g., microbial, chemical, physical) associated with each step of the food chain, making it an ideal resource.